3D thermal model and experimental validation of a low voltage three-phase busduct. (5th January 2017) - Delgado, F.; Renedo, C.J.; Ortiz, A.; Fernández, I.; Santisteban, A.
Highlights: A thermal numerical model of a busbar trunking system has been developed. The model has been applied to different geometries with different electrical loads. The numerical results have been compared with experimental test data. The model can be employed in the first steps of the design of the busbar. Abstract: The thermal behavior of an industrial low voltage non-segregated three-phase busduct was analyzed by means of the comparison of a 3D numerical model with experimental results. This model has been carried out using COMSOL Multiphysics, software based on finite element method. The numerical model replicates the short-circuit test, using the same geometry configuration and the boundary conditions of the laboratory in which this assay was carried out. The standard IEC 61439 was applied, both in test and model, in order to obtain the steady state temperatures in several parts of the busbar system. As a result of the data comparison can be concluded that the experimental test was replicated by the numerical model with sufficient accuracy. The temperature differences between simulation results and those of the heating tests were in a narrow range. On the other hand, a sensitivity analysis was carried out with the intention to study the influence of sensors positioning on the temperature measurement in the laboratory test, thus concluding no high precision was needed in the location of the temperature meters. As a final conclusion of this study, it is needed to point out that the numerical model has the enough exactness to be used in the first steps of the busbar design.